2006
DOI: 10.1007/s11430-004-5317-8
|View full text |Cite
|
Sign up to set email alerts
|

SHRIMP zircon U-Pb age and significance of Early Paleozoic volcanic rocks in East Kunlun orogenic belt, Qinghai Province, China

Abstract: Early Paleozoic volcanic rocks in Nuomuhong area occurred as basalt slice and meta-volcanic slice. SHRIMP zircon U-Pb dating of the basalt slice and the meta-volcanic slice show that the age of the basalt slice is 419±5 Ma, and that of the meta-volcanic slice is 401± 6 Ma. These ages directly testify that there existed Early Paleozoic ocean-continent transform in East Kunlun, the basalt slice was formed in an extensional mid-ocean ridge setting and the meta-volcanic rock slice was formed in an extrusion subduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(14 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…1). It underwent Early Palaeozoic and Early Mesozoic subduction and collision processes, during which time the Nuomuhong-Qingshuiquan and the Anyemaqen-Buqingshan suture zones were formed successively (Yang et al 1996;Bian et al 2004;Zhu et al 2006). The eastern Kunlun Orogen consists traditionally of three tectonic units, the Northern, Middle and Southern Zones, separated by the North and Central Kunlun faults, respectively (Jiang et al 1992).…”
Section: Geological Setting and Geology Of The Plutonsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). It underwent Early Palaeozoic and Early Mesozoic subduction and collision processes, during which time the Nuomuhong-Qingshuiquan and the Anyemaqen-Buqingshan suture zones were formed successively (Yang et al 1996;Bian et al 2004;Zhu et al 2006). The eastern Kunlun Orogen consists traditionally of three tectonic units, the Northern, Middle and Southern Zones, separated by the North and Central Kunlun faults, respectively (Jiang et al 1992).…”
Section: Geological Setting and Geology Of The Plutonsmentioning
confidence: 99%
“…It constitutes an important component of the Early Palaeozoic Nuomuhong suture zone (Wang, Jia & Zhu, 2003, pp. 1-98;Zhu et al 2006). The Devonian sedimentary rocks are typical molasse deposits and include conglomerates, sandstones, mudstones and rarely volcanic rocks.…”
Section: Geological Setting and Geology Of The Plutonsmentioning
confidence: 99%
“…Especially, it is debated when the postcollisional extension regime was initiated. For example, Zhu and Lin [7] suggested that subduction of the oceanic crust lasted until the Early Devonian, while Dong and He [8] argued that the Proto-Tethys Ocean in the EKOB had closed and that the postcollisional extension setting occurred since the Early Devonian. Zhou and Dong [9] suggested that the postcollisional extension regime was initiated during the Late Ordovician.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, it is still debated when the post-collision extension regime was initiated. For example, Zhu, Lin [7] suggested that subduction of the oceanic crust still existed during the Early Devonian, while Dong, He [8] argued that the Proto-Tethys Ocean in the EKOB had been closed and that the post-collision extension setting occurred since the Early Devonian. Zhou, Dong [9] considered that the post-collision extension regime was initiated during the Late Ordovician.…”
Section: Introductionmentioning
confidence: 99%